(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In the world of marketing, packaging of products is a very vital word. No doubt, it plays a significant role in effective marketing of products, especially in the global market. In marketing, the consumer is said to be king, and as such, much effort is made to draw the attention of this king through packaging in the internal scene. Many firms have confirmed that packaging has been playing an estimable role in consumer perception and the selective retention of made in Nigeria products in the global market. Thus, this paper examines the impact of packaging made in Nigeria on products for the global market.